Beethoven's immortal beloved : solving the mystery - Walden, Edward, 1933- (Scarecrow Press, 2011)
In 1812, Ludwig van Beethoven wrote three letters to an unnamed woman, whom he called "Immortal Beloved." The letters were discovered after Beethoven's death and ever since their discovery, there has been speculation regarding whom that Immortal Beloved might have been. In Beethoven's Immortal Beloved: Solving the Mystery, Edward Walden carefully and meticulously presents his case that the woman who Beethoven loved was Bettina Brentano, an artistic and talented musician in her own right. Setting the foundation for his argument, Walden begins the book with a general historical and sequential n.